(3LRA ajg NeSI CMGOjKs - (3eMeO Hf YHO Gddg Hf eMeO GdeYGaQj GdETHjdj GdeGdcj, GdbGVj CHh HcQ GHf GdYQHqj , J (B543 (3g` s ((3YKeGf Hf eMeO Hf YKeGf GdYLei GdbfbGRi s)
(3ChdgG (B:s
(3CNHQfG GdTjN CHh eMeO YHO GdeDef Yf CfS Hf eGdc bGd (B: (3cGf GdfHi Udi Gddg Ydjg hSde EPG OYG QLdkG Edi GdcJGHI cGf jbhd Cdb GdOhGI GdMOjK s
(3BNQgG (B:s
(3hYdjc HMSf GdNdb aEf MSf GdNdb ef CNdGb GdLfI MOKfG GdbGVi CHh eQhGf Hf eQI ELGRI HSfOg GdeJbOe BNQg s
(3GdfSNI HgG MhGTs
(3gPG GdeDda djS gh CHj HcQ Hf GdYQHi GdeYQha TGQM GdJQePi HBNQgG SeGYGJ cKjQI Ydi GdMGaX YHO GdeDef Hf Nda GdOejGWi hcJH UMI GdSeGY HNWg (B688 (3hai BNQgG NW Jbi GdOjf GdSHcis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B230 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B242s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdMOjK h GdeUWdMs